Is schooling forever doomed with child labor around? An analysis using Philippine time use data - Dacuycuy, Connie Bayudan- (Animo Repository, 2013)
Using a rich survey data collected in the southern part of the Philippines, this paper aims to study the effect of child labor on the child's schooling outcomes. Results indicate that the efficient allocation of time can offset the impact of an increase in the child's work hours. I f child labor cannot be prevented, the paper offers some directions on the type of public goods the government can provide.